2022
DOI: 10.3389/fphar.2022.920939
|View full text |Cite
|
Sign up to set email alerts
|

Homologous Recombination Pathway Alternation Predicts Prognosis of Colorectal Cancer With Chemotherapy

Abstract: Background: Chemotherapy is the basic treatment for colorectal cancer (CRC). However, colorectal cancer cells often develop resistance to chemotherapy drugs, leading to recurrence and poor prognosis. More and more studies have shown that the Homologous recombination (HR) pathway plays an important role in chemotherapy treatment for tumors. However, the relationship between HR pathway, chemotherapy sensitivity, and the prognosis of CRC patients is still unclear.Methods: We collected 35 samples of CRC patients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…COAD patients show high morbidity and mortality rates because of metastasis, cancer recurrence, and chemotherapy resistance [22]. An increasing number of studies have suggested that a typical characteristic of malignancy is abnormal one-carbon metabolism, which play key role in protein synthesis, especially, methionine serves as the primary methyl source for DNA, protein, and lipid methylation via S-adenosyl-methionine (SAM) [23].…”
Section: Discussionmentioning
confidence: 99%
“…COAD patients show high morbidity and mortality rates because of metastasis, cancer recurrence, and chemotherapy resistance [22]. An increasing number of studies have suggested that a typical characteristic of malignancy is abnormal one-carbon metabolism, which play key role in protein synthesis, especially, methionine serves as the primary methyl source for DNA, protein, and lipid methylation via S-adenosyl-methionine (SAM) [23].…”
Section: Discussionmentioning
confidence: 99%